2010
DOI: 10.1111/j.1471-4159.2010.06931.x
|View full text |Cite
|
Sign up to set email alerts
|

PPAR activation has dichotomous control on the expression levels of cytosolic and secretory phospholipase A2 in astrocytes; inhibition in naïve, untreated cells and enhancement in LPS‐stimulated cells

Abstract: J. Neurochem. (2010) 115, 399–410. Abstract Despite the importance of cytosolic phospholipase A2 type IVA (cPLA2) and secretory PLA2 (sPLA2) in physiological and pathological responses of astrocytes in inflammatory conditions, the regulation of the expression of these genes is still unclear. Both genes have peroxisome proliferator‐activated receptors (PPAR) binding sites in their promoters. The role of synthetic PPAR agonists in the regulation of gene expression in naïve and lipopolysaccharide (LPS)‐stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Agonists of PPARa and PPARc have been reported to possess anti-inflammatory activity in astrocytes (Xu and Drew 2007;Bernardo and Minghetti 2008), and there is evidence that PPARc is activated by CLA in animal models and clinical studies (Reynolds and Roche 2010). Interestingly, a recent in vitro study (Sergeeva et al 2010) showed that the expression of cPLA 2 and sPLA 2 was inhibited by PPARa and PPARc agonists in naïve astrocytes, but was increased by PPARc activation in lipopolysaccharide (LPS)-stimulated astrocytes. Thus, if the anti-inflammatory properties of CLA reported in several studies are mediated by the activation of PPARc, the resulting effects on the activity and gene expression of PLA 2 groups in brain tissue seem to depend on the inflammatory status of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists of PPARa and PPARc have been reported to possess anti-inflammatory activity in astrocytes (Xu and Drew 2007;Bernardo and Minghetti 2008), and there is evidence that PPARc is activated by CLA in animal models and clinical studies (Reynolds and Roche 2010). Interestingly, a recent in vitro study (Sergeeva et al 2010) showed that the expression of cPLA 2 and sPLA 2 was inhibited by PPARa and PPARc agonists in naïve astrocytes, but was increased by PPARc activation in lipopolysaccharide (LPS)-stimulated astrocytes. Thus, if the anti-inflammatory properties of CLA reported in several studies are mediated by the activation of PPARc, the resulting effects on the activity and gene expression of PLA 2 groups in brain tissue seem to depend on the inflammatory status of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant and anti-inflammatory actions of PPAR δ agonists have been observed in a variety of cell types, including astrocytes and microglia [3235]. In particular, PPAR δ can activate transcription of antioxidant genes, including catalase and superoxide dismutase (SOD) [3638].…”
Section: Stroke-induced Brain Injurymentioning
confidence: 99%
“…As the authors noted, LPS stimulates NF- κ B and activator protein-1 (AP-1), which PPARs have been shown to transrepress. It is possible that in this model LPS-induced activation of NF- κ B and AP-1 is acting to transrepress PPAR δ [35]. Furthermore, LPS-induced Cox-2 expression in rat primary astrocytes may be modulated, in part, by PPAR δ .…”
Section: Astrogliosismentioning
confidence: 99%
“…Cortical bone formation in the knock-out mice is also increased. In fact, Pparγ is a protein with complex mechanism, which could inhibit certain gene expression levels in untreated cells and enhance these in LPS-stimulated cells (42). Thus, it was suggested that the inhibition of Pparγ gene expression by LPS in undifferentiated BMSCs may reflect a potential osteogenic role.…”
Section: Discussionmentioning
confidence: 99%